ADELMAN, Jeremy: Sovereignty and Revolution in the Iberian Atlantic. Princeton: Princeton University Press, 2006, 409 pp. - Brownrigg-gleeson Martínez, José-Shane (Studia Historica. Historia Contemporánea, 2011)
Reseña